RELIGIOSITY AND OBEDIENCE HEALTH PROTOCOLS COVID-19: A POSITIVE CORRELATION IN MEDAN-NORTH SUMATERA - Suryani, Des; Siregar, Pinta Pudiyanti (Universitas Muhammadiyah Sumatera Utara, 2021)
The COVID-19 pandemic, which is running slowly but surely, demands that people obey health protocols. In other views, Islam has taught how a Muslim should deal with the epidemic. Various factors that might affect public compliance with COVID-19 health protocols include demographic factors, knowledge of COVID-19, health status, and religiosity. Various studies showed that there was still controversy related to it. This study aimed to determine the correlation between compliance with the COVID-19 Health protocol with knowledge of COVID-19, self-health perception, and religiosity for the Muslim community in North Sumatera, Indonesia. This study was conducted between mid of October to mid-November 2020 on the Muslim population living in Medan City and Deli Serdang District, the most prevalent places for the spread of COVID-19 in North Sumatra. The questionnaires were distributed randomly to the online recitation group in the red zone in North Sumatra. Data collected by google form is distributed via the WhatsApp (WA) application. The results of the study were among 225 participants in the study, those who adhered to the health protocol were 125 people (55.6%), and the level of good religiosity was 120 people (53.33%). This study found that people who adhere to health protocols are related to older age, female gender, higher education, private workers, better knowledge of COVID19, and high religiosity. Religiosity is positively correlated with compliance with health protocols during the COVID-19 pandemic. In Logistic Regression analysis, religiosity turns out to be a good predictor for increasing compliance. Thus there needs to be a parallel effort between increasing knowledge about COVID-19 and community religiosity so that prevention efforts will be even better in the future